Long-stay institutions for the elderly: a review (Research, Society and Development, 2022)
The emergence and spread of long-stay institutions for the elderly (ILPIs) is linked to the demographic increase of this population in Brazil. This study aims to analyze long-stay institutions within the context of the demographic transition and the factors that lead elderly people to institutionalize. National scientific articles were used, available in full in the Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Research, Society and Development journals, published in the last five years. Adhering through the descriptors/key words: “elderly person”, “ILPI”, “housing”, combined with the Boolean operator “AND”. Firstly, data on population aging was exposed, followed by a brief historical perspective of Long-Term Institutions and ending with the process of institutionalization of the elderly in them. It was concluded that although there are definitions and configurations on how LTCFs should work, an in-depth study of the physical and behavioral needs of the elderly is necessary, in order to restructure the environment of LTCFs, places that have become the housing destination for growing demand from older people. The institutionalization process and the experience of the elderly in the institution are factors for the study of improvements in the quality of care provided to the elderly.